Chromatography-the Ultimate Analytical Tool (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Since its early introduction by the Russian botanist Mikhail Semyonovich Tsvet, chromatography has been undoubtedly the most powerful analytical tool in analytical chemistry. Separation, qualitative analysis, and quantitative analysis can be achieved by choosing the right conditions. Thus, numerous gas chromatographic, liquid chromatographic, and supercritical fluid chromatographic methods have been developed and applied for most types of samples and most kinds of analytes. Additionally, older varieties such as paper chromatography and thin-layer chromatography were pioneer analytical techniques in many laboratories. Especially when hyphenated to spectrometric techniques, chromatography also allows the identification of separated analytes in a single run. Highly sophisticated equipment can answer all analytical problems very quickly. Chromatographers cooperate with many scientific fields and give their lights to medical doctors, veterinarians, food scientists, biologists, dentists, archaeologists, etc. In this Special Issue, analytical chemists were invited to prove that chromatography-based separation techniques are the ultimate analytical tool and their significant contribution is reflected in ten interesting articles.